PENILAIAN DAYA DUKUNG LINGKUNGAN WISATA DI TAMAN WISATA ALAM (TWA) MANGROVE ANGKE KAPUK JAKARTA - Nova Eviana; Lenny Yusrini (Eduturisma, 2019)
The development of tourism and the great numbers of visitors not only have positive impacts but also raise concerns about the negative impacts of visitor activities on the environment and the challenges of how to achieve sustainable tourism. It is therefore important to measure the tourism carrying capacity. This study aims to measure visitors' perceptions and to analyze the tourism carrying capacity in the Angke Kapuk Mangrove Natural Park, covering ecological, social and economical aspects. Data are collected using questionnaires with accidental sampling technique for visitors and local communities as respondents. Research data are then analyzed using descriptive analysis. The result shows that visitors perceive positively on the aspects of accessibility, attractions, accommodation, tourist activities, and amenities. A negative assessment is given by visitors to the availability of souvenir shops and restaurant. The Gini index coefficient is worth 0.9742 which means that there is a high imbalance in the distribution of visitors. Higher inequality tends to raise high vulnerability/ potential damage of the environment. Local communities are actively involved in managing tourism site, especially as craft level personnels. Economically, Angke Kapuk mangrove natural park provides employment and business opportunities for local residents. The provision of local souvenirs is needed to improve positive perception toward the tourist object. In order to guarantee sustainable tourism, manager of Angke Kapuk Mangrove natural park should carry out the conservation education through interpretation programs, and rearrange tourists’ attractions and activities of each zone.